EFFECT OF NON-GENETIC FACTORS ON THE QUALITY OF FROZEN SEMEN OF CROSSBRED HOLSTEIN FRIESIAN BULLS - GOPINATHAN, A; SIVASELVAM, S N; KARTHICKEYAN, S M K; KULASEKAR, K (The Indian Journal of Animal Reproduction, 2022)
Sixty five frozen semen samples of 14 crossbred Holstein Friesian bulls were subjected to quality assurance tests such as post-thaw motility, post-thaw incubation survival, hypo-osmotic swelling (HOST) and acrosome integrity. The data were statistically analyzed to study the effect of farm (I and II), ejaculate (I and II), period (2007-2014) and season (summer, winter and northeast monsoon) on the frozen semen quality using general linear model. Post-thaw motility and post-thaw incubation survival of spermatozoa was highly affected (p<0.01) by ejaculate, period and season, whereas, HOST was affected by period, and acrosome integrity was affected by ejaculate and period. In brief, non-genetic factors had impact on the quality of frozen semen of crossbred Holstein Friesian bulls.